Financial development, human capital development and climate change in East and Southern Africa - Olatunji Abdul Shobande; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Africa is currently experiencing both financial and human development challenges. While several continents have advocated for financial development in order to acquire environmentally friendly machinery that produces less emissions and ensures long-term sustainability, Africa is still lagging behind the rest of the world. Similarly, Africa's human development has remained stagnant, posing a serious threat to climate change if not addressed. Building on the underpinnings of the Environmental Kuznets Curve (EKC) hypothesis on the nexus between economic growth and environmental pollution, this study contributes to empirical research seeking to promote environmental sustainability as follows. First, it investigates the link between financial development, human capital development and climate change in East and Southern Africa. Second, six advanced panel techniquesare used, and they include: (1) cross-sectional dependency (CD) tests; (2) combined panel unit root tests; (3) combined panel cointegration tests; (4) panel VAR/VEC Granger causality tests and (5) combined variance decomposition analysis based on Cholesky and Generalised weights. Our finding shows that financial and human capital developments are important in reducing CO2 emissions and promoting environmental sustainability in East and Southern Africa.
Keywords: G21; I21; I25; O55; Q54; 330; Financial Development; Human Capital; East and Southern Africa; Climate Change